Cloud data security and various security algorithms. Issue 1 (August 2021) - Tyagi, Kanika; Yadav, S.K; Singh, Mayank
Abstract: The term Cloud computing is a most trending and promisingtechnology. It is the most basic need for many organizations. Cloud technology has many advantages as user can access the files from anywhere over the internet. It has also a very known feature of using the resources according to their demand and user does need to pay extra charges for the unused resources. In Cloud Computing user do not need to carry all their documents with them as cloud access is global. But as Cloud computing means sending data over internet so sometimes there may be security issues and threat of intruder attack at the time of data transmission. As traditional banking industry is totally changed and now the total control in the hand of customer rather than the bank. In banking industry cloud computing provides various features viz; cost saving, business continuity, business agility and time saving. but as data in bank is the most crucial data so cloud security is the first priority for every bank before adopting cloud. security at cloud is the biggest obstacle for the banking industry to adopt this trending technology and its services. So there is need to provide security to the cloud. This paper aims on cloud basic methodology and analyze some security algorithms and their applicability in cloud banking environment.